Dynamical Codimension – 2 Brane in a Warped Six Dimensional Space-time - Lien, Phan Hong (Communications in Physics, 2018)
In this paper we present the Einstein equation extended in six-dimensions (6D) from the formation of codimension-2 brane, which is created by a 4-brane and 4-anti brane moving in the warped 6D “bulk” space-time. The system of equations of motion for the dynamical codimension - 2 brane has been derived to describe the cosmological evolution on the probe branes. Some cosmological consequences are investigated.